THE INFLUENCE OF CONTEXT ON PRIVACY CONCERN IN SMART TOURISM DESTINATIONS - Afolabi, Olayinka Olasumbo; Adeshola, Ibrahim; Ozturen, Ali; Ilkan, Mustafa (PEOPLE: International Journal of Social Sciences, 2020)
A study of existing literature research shows that mobile application development and usage is now an essential aspect of everyday life. The privacy concerns of the users towards the application provided on the mobile devices that make use of their data is still a problem. This study highlights the need for mitigating the privacy concern of the users towards mobile applications used in smart tourism destinations and develops a framework based on the review of previous research and literature. The framework proposed by this study supports the relationship between personal beliefs and the environment, with the moderating effect of use context. This research is empirically driven and discusses the relationships between the study item’s privacy concern, use context, and behavioral intentions within the context of the mobile application.